Utilization of ferronicle slag for the manufacture of rotary kiln lining refractories - Muhammad Ridwan Septiawan; Angga Tegar Setiawan; Muhammad Alfian; Jumaddil Hair; Joko Sulistyo (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2026)
Ferronickel slag waste from the nickel ore processing industry can be used as a refractory raw material for the inner wall lining of rotary kilns. However, the use of this waste still needs to be studied for its properties to meet the standards for its use in the industry. The purpose of this study was to find the optimal composition of a refractory mixture consisting of ferronickel slag, magnesium oxide (MgO), and aluminum oxide (Al2O3). The percentage composition of ferronickel slag and MgO was changed, while Al2O3 remained constant. The characterization of the refractories that had been made was carried out through a series of tests consisting of chemical composition testing using X-ray Fluorescence (XRF), porosity testing, bulk density, permanent linear change (PLC), and cold crushing strength (CCS). The results of the analysis showed that the ferronickel slag used as the main material in this study contained silica (SiO₂), magnesium oxide (MgO), and iron oxide (Fe₂O₃) which supported the properties of the refractories that had been made. The optimal refractory composition is 90% slag and 10% MgO, resulting in a porosity of 25.56% and a bulk density of 1.74 g/cm³, indicating a balance between strength and thermal insulation. The PLC green value of -0.8667% and the PLC dried value of -0.1177% indicate good dimensional stability. The CCS test for the best composition produces a cold compressive strength of 1.44 MPa. The study indicate that refractories have thermal and mechanical resistance that supports their use as rotary kiln lining materials.